Considerations Around the Classification of Parts of Speech and Inter-Speech Questions - Meytikhanyan, Parandzem (Bulletin of Yerevan University B: Philology, 2022)
In the article the author for the first time made the subject of the study parts of speech and intra-speech issues, briefly referring to Dionysius of Trakais, Roman and Latin grammarians, and to the grammatical views of the giants of Armenian linguistic thought - M. Abeghian, Gr. Acharyan, G. Jahukyan, S. Abrahamyan, Ed. Agayana, St. Palasanyan, G. Sevak, Ar. Gharibyan, H. Barseghyan and others, in more detail - to the classification of parts of speech, especially to opposite views on the characterization of the Pronoun as a part of speech. The author of the article in certain cases expresses her own position.The main purpose of the study is to present the parts of speech Pronoun, Adverb in the modern linguistic understanding in school normative grammar as possible simply and accessible, and also to observe to the genealogy of parts of speech.
Keywords: branch of linguistics; school normative grammar; grammatical construction; parts of speech; noun; adjective; numeral; pronoun; interjection; modal words; assonance; semantic-functional feature; multiplication of parts of speech